The making and re-making of high modernist towns in the Circumpolar North. (December 2022) - Avango, Dag; Pashkevich, Albina; Rodon, Thierry
Highlights: The challenges of building attractive settlements for natural resource oriented industries in the Arctic, capable of attracting employees from elsewhere, analyzed through the lens of high modernist settlements in the post WW2-era. Describe and explain the fate of high modernist architecture and settlement planning by comparing the development of mining towns in Sweden and Quebec in Canada. Focus on architecture and planning designs by renowned architect Ralph Erskine, combining rational functionalist principles of industrial production, with an idea of a humane modernism, adapted to the Arctic. Discuss why Erskine´s designed were successful in Canada and unsuccessful in Sweden, providing the basis for making informed decisions on how to create attractive settlements in the present, to enable the growth of green industries in the far north. Abstract: In this article we explore the fate of high modernist architecture and settlement planning in the North, through the lens of mining towns in Sweden and Quebec. After WW2, cities across the world were subject to a wave of restructuring in accordance with high modernist ideals. The circumpolar north became the subject of some of the most radical examples, often described as utopian. In the Swedish Arctic, a renowned architect Ralph Erskine played a leading role. He combined functionalist principles, with ideas of creating settlements protecting inhabitants from harsh Arctic conditions, in harmony with the environment. Erskine...s ideas were implemented to a different extent in Kiruna and Svappavaara in north Sweden in the 1960's and in Fermont, Quebec, in the early 1970...s. Our aim is to understand the challenges of creating industrial settlements in the Arctic, with the capacity to attract employees that are needed for resource extraction and other industries. While Erskine's architecture in Svappavaara and Kiruna will be demolished, the wall shaped town in Fermont is still intact and expanding. By comparing and highlighting differences, we call attention to the threat of demolition of legacies of an era that has yet to be defined as cultural heritage.